The Effect Of Moderate To Intense Physical Activity On Blood Sugar And Body Weight - Raouan, Mohamed (sports creativity, 2025)
study focused on discovering the relationship between moderate physical activity and the biological and physical variables that affect a group of people with glucose tolerance ranging in age from 30 to 50 years, where laboratory tests were conducted at the level of the laboratory of Al-Wamiam Hospital and physical tests at the level of 18 February stadium in Laghouat. A physical program for running and brisk walking was prepared for this purpose. For the purposes of this study, the researcher used the experimental approach. After statistical treatment with spss program and data analysis, the researcher reached the following results: There are statistically significant differences between the pre and post tests and in favor of the post test for each variable Among the targeted variables in the study, this indicates that regular physical activity reduces the risk of obesity and high blood sugar levels and delays the emergence of health problems and regulates digestion